White oleander - Fitch, Janet; Warner Bros. Pictures; Pandora Film (Firm).; Warner Home Video (Firm). (Burbank, Calif. Warner Home Video, 2010)
Ingrid, a smart, free-spirited, and somewhat narcissistic artist kills her deceitful lover in a crime of passion. Even while serving a prison sentence, she exerts control over her adoring teenage daughter, Astrid, who's forced to spend her teenage years in a series of foster homes before becoming her own person. Explores the strange relationship of Ingrid and Astrid, and includes Astrid's relationship with her foster mothers. At first merely an appendage of her mother, Astrid develops as a result of her peripatetic adolescence.
Library has: VDR-1656 (2 VCDs)
Based on the novel by Janet Fitch.
Originally released as a motion picture in 2002.
Special features include: Commentary by director Peter Kosminsky, producer John Wells and original novel author Janet Fitch; Additional scenes; Behind-the-scenes visits with cast and creators: "The journey of White oleander" and "The making of White oleander"
Director of photography, Elliot Davies ; editor, Chris Ridsdale ; music, Thomas Newman ; costume designer, Susie DeSanto ; production designer, Donald Graham Burt
Alison Lohman, Robin Wright Penn, Michelle Pfeiffer, Renée Zellweger, Billy Connolly, Patrick Fugit, Cole Hauser, Noah Wyle.
Keywords: Mothers and daughters -- Drama; Children of prisoners -- Drama; Foster mothers -- Drama; DVD-Video discs